High-Flow Nasal Cannula Oxygenation pada Pasien Lanjut Usia dengan Kegagalan Pernafasan Akut Terkait SARS-CoV-2: High-Flow Nasal Cannula Oxygenation in Older Patients with SARS-CoV-2-Related Acute Respiratory Failure - Faris Putra Haryanto; Khadafi Indrawan; Ari Wahyuni (CV. Jasa Sukses Abadi, 2021)
Currently, In this World, many cases about comparing the mortality and comfort associated with method of high-flow nasal cannula oxygenation (HFNCO) and high-concentration mask (HCM) in older SARS-CoV-2 infected patients done hospitalized in non-intensive care units. In this retrospective cohort study, author included all consecutive patients aged 75 years and older who were hospitalized for acute respiratory failure in either an acute geriatric unit or an acute pulmonary care unit, and tested positive for SARS-CoV-2. This journal compared the in-hospital prognosis between patients treated with HFNCO and patients treated with HCM. To determinate another bias factor, this journal created a propensity score for HFNCO. From March 2020 to January 2021, 67 patients (median age 87 years, 41 men) were hospitalized with SARS-CoV-2-related akut respiratory failure, of whom 41 (61%) received HFNCO and 26 (39%) did not. Age and comorbidities did not significantly differ in the two groups, whereas clinical presentation was more severe in the HFNCO group (NEW2 score: 8 (5–11) vs. 7 (5–8), p = 0.02, and Sp02/Fi02: 88 (98–120) vs. 117 (114–148), p = 0.03). Seven (17%) vs. two (5%) patients survived at 30 days in the HFNCO and HCM group, respectively. Overall, HFNCO was significantly associated with greater survival (adjusted hazard ratio (AHR) 0.57, 95% CI 0.33–0.99; p = 0.04). HFNCO use was associated with a lower need for morphine (AHR 0.39, 95% CI 0.21–0.71; p = 0.005), but not for midazolam (AHR 0.66, 95% CI 0.37–1.19; p = 0.17). In conclusion, HFNCO use in non-intensive care units may reduce mortality and discomfort in older inpatients with SARS-CoV-2-related akut respiratory failure.